Farmers’ adoption and willingness to pay for post-harvest technologies in Tanzania: policy implication for enhancing food security - Mwaijande, Francis (Journal of Postharvest Technology, 2017)
This study was conducted in Morogoro, Iringa, Njombe, Mbeya and Songwe regions in Tanzania. The main objective of the study was to  establish post-harvest technology (PHTs) adoption and willingness to pay for PHTs. It was found that farmer ‘awareness on post-harvest  technologies is increasing, especially on hermetic PICS Bags. However the adoption to PHTs is limited by price and availability close to their  localities. Most farmers are willing to pay at an average of 4,000 but some sellers are selling more than that price. On preference, many end  users prefer PICS for the reason that it is mostly available and mostly popularized. Preference is also determined by price affordability,  availability and proximity to suppliers. The study concludes that PHTs have received high acceptance by farmers who have awareness and  knowledge. However, the technology uptake is limited mainly by price affordability, availability and proximity. The present study recommends  for subsidizing PHT products with manufacturers to reduce the current market price and increase more awareness campaigns through  agrodealers, physical visits to farmers and farmers associations to increase demand for PHTs among farmers / farm associations as well as  timely distribution of PHTs (hermetic bags) before the harvesting season in May-June in the Southern Highland regions.
Keywords: Farmers; postharvest technology; determinants; adoption,; willingness